AVALIAÇÃO DA QUALIDADE PERCEBIDA EM SERVIÇOS EDUCACIONAIS: PROPOSTA DE UMA ESCALA - Verônica Paludo Bressan (Universidade Federal de Santa Catarina, 2015)
The aim of this research is to develop and validate a scale in order to measure the quality perceived by undergraduate students in educational services. To carry out the work, was developed a bibliographic research about the concepts and features related to perceived quality, quality in higher education and ways to measure service quality, identifying the need to develop a specific scale for educational services in view of the tools found in the literature treated services in a general terms. To develop the scale so followed the steps suggested by Churchill in 1979, by cond ucted interviews with 17 students, in the qualitative exploratory research, and applied 410 questionnaires in students in the quantitative descriptive stage, consisting of two samples, for test and for validation. The results obtained by conducting explora tory factor analysis and confirmatory factor analysis demonstrated the reliability of the proposed scale, allowing its application in the context of higher education’s managerial. The final scale was composed by 21 indicators, and 6 dimensions: curriculum organization, professors, research and extension learning, administrative organization, infrastructure and additional services. This study has academic’s implications, because that collaborates with the discussion and on the indicators that make up the per ceived quality of educational services. Also, has a managerial implication, because it presents a new tool that can be used in higher education institutions as a way to qualify the delivery of services to the students.